A study on experimental characteristics of microwave-assisted pyrolysis of palm kernel shell / Muhammad ‘Azim Jamaluddin et al. - Jamaluddin, Muhammad ‘Azim; Ismail, Khudzir; Ab Ghani, Zaidi; Mohd Ishak, Mohd Azlan; Abdullah, Fauzi; Idris, Siti Shawalliah; Mohammed Yunus, Mohammed Faisal; Tahiruddin, Shawaluddin; Mohd Hakimi, Noor Irma Nazashida (Universiti Teknologi MARA, Perlis, 2012)
Pyrolysis of palm kernel shells was successfully done via microwave-assisted carbonization system with different microwave power levels at a fixed reaction time, nitrogen flow rate and sample mass of 30 minutes, 150 mL/min and 40 g, respectively. Temperature profiles, temperature rising rate and the char properties were analyzed in order to determine optimum conditions of the pyrolysis process using thermogravimetric, elemental and FTIR analysis. Increasing microwave power levels resulted in increasing of maximum reaction temperature as well as the temperature rising rate, with lower char production. The chars obtained at power 300, 600 and 1000 Watt have comparable properties in terms of fixed carbon, volatile matter contents and the calorific values with an average values of 60 wt%, 35 wt % and 30 MJ/kg, respectively. Evidently, low microwave power of 300 Watt was sufficient enough for a complete pyrolysis of palm kernel shells, thus proving that 300 Watt is the best power to obtain high quality chars for further applications in the industry.